Ta fascynująca przestrzeń pomiędzy. Notatki na marginesie książki Mockumentary. Próba określenia istoty zjawiska - Wnuk, Agnieszka (Załącznik Kulturoznawczy, 2018)
The text is a commentary to the book by Tomasz Baldziński and Dorota Dłużniewska-Urban Mockumentary. Próba określenia istoty zjawiska [Mockumentary. An Attempt to Define the Essence of the Phenomenon]. The authoress focuses on the phenomenon of mixing the genres, and in particular of combining the conflicting elements of fiction and documentarism in contemporary cinema.